The concept of colour as a grammar problem in Wittgenstein - Igansi, Luca Nogueira (Revista PHILIA | Filosofia, Literatura & Arte, 2019)
This essay aims to provide conceptual tools for the understanding of Wittgenstein’s theory of color as a grammar problem instead of a phenomenological or purely scientific one. From an introduction of his understanding of meaning in his early and late life, his notion of grammar will be analyzed to understand his rebuttal of scientific and phenomenological discourse as a proper means for dealing with the problem of color through his critique of Goethe. Then Wittgenstein’s take on color will become clear as his sympathy for Runge, the painter that Goethe criticizes, is analyzed to understand color as a language-game regarding kinds of colors as numbers and geometrical figures, in that grammar rather than experience is used to acknowledge them. Keywords: Meaning. Language-games. Grammar. Color. Perception.